Design of Progress Logbook for Operational and Watchroom Logbook Recording at YIA Airport - Dirgantarum Ratri Fakhriyyah (Dinasti International Journal of Education Management And Social Science, 2025)
Aviation safety is a crucial aspect that requires the support of a reliable information system, particularly in the Airport Rescue and Fire Fighting (ARFF) unit, which plays a key role in handling airport emergencies. At Yogyakarta International Airport (YIA), activity reports and watchroom monitoring are still recorded manually, making the process prone to errors, delays, and inefficiencies. This study aims to design and develop ARFF Progress Logbook, a web-based portal that facilitates daily report recording and real-time, integrated monitoring of watchroom activities. The research method used is Research and Development (R&D) with the Waterfall model, covering the stages of needs analysis, system design, implementation, as well as testing and evaluation based on ISO 25010 standards. System testing was conducted through a functionality checklist and by distributing questionnaires to ARFF personnel and IT experts, focusing on aspects of functional suitability, usability, compatibility, and performance efficiency. The results show that all main features of the Progress Logbook system have functioned well, with the system obtaining an average score above 85% across all ISO 25010 evaluation aspects, thus being categorized as highly feasible for implementation. The system improves recording efficiency and monitoring effectiveness in ARFF operations, supporting integrated, responsive, and modern aviation safety standards.